Music and 25% glucose pain relief for the premature infant: a randomized clinical trial (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: to analyze the total Premature Infant Pain Profile scores of premature infants undergoing arterial puncture during music and 25% glucose interventions, and to assess their association with neonatal and therapeutic variables. METHOD: a randomized clinical trial with 80 premature infants; 24 in the Experimental Group 1 (music), 33 in the Experimental Group 2 (music and 25% glucose), 23 in the Positive Control Group (25% glucose). All premature infants were videotaped and a lullaby was played for ten minutes before puncture in Experimental Groups 1 and 2; 25% glucose administered in Experimental Group 2 and the Positive Control Group two minutes before puncture. RESULTS: 60.0% of premature infants had moderate or maximum pain; pain scores and intervention groups were not statistically significant. Statistically significant variables: Experimental Group 1: head and chest circumference, Apgar scores, corrected gestational age; Experimental Group 2: chest circumference, Apgar scores, oxygen therapy; Positive Control group: birth weight, head circumference. CONCLUSION: neonatal variables are associated with pain in premature infants. Brazilian Registry of Clinical Trials: UTN: U1111-1123-4821.